Understanding Proactive Customer Orientation Construct Development and Managerial Implications - Herhausen, Dennis (Gabler, 2011)
Dennis Herhausen examines how managers can successfully probe latent needs and uncover future needs of customers, labeled as proactive customer orientation. To answer this question, three stages of research are deployed: (1) An exploratory study investigating two different dimensions of proactive customer orientation, (2) a quantitative study investigating consequences, antecedents, and factors that moderate the effects of proactive customer orientation, and (3) a qualitative study investigating situation-specific recommendations on how to increase proactive customer orientation. Overall, a systematic change process is developed to guide managers that aim to increase their company's proactive customer orientation.